Disease Severity and Motor Impairment Correlate With Health-Related Quality of Life in AP-4-Associated Hereditary Spastic Paraplegia. (August 2021) - Jordan, Catherine; Geisel, Gregory; Alecu, Julian E.; Zhang, Bo; Sahin, Mustafa; Ebrahimi-Fakhari, Darius
Abstract : Objective: AP-4-associated hereditary spastic paraplegia (AP-4-HSP) is a childhood-onset neurogenetic disease and mimic of cerebral palsy. Data on health-related quality of life (HRQoL) are lacking. To establish a metric for HRQoL and caregiver priorities, we used the Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD) questionnaire to assess HRQoL in correlation with disease severity in 64 patients with AP-4-HSP. Methods: A cross-sectional analysis of caregiver-reported HRQoL was performed using the CPCHILD questionnaire in combination with a detailed clinical characterization. Results: HRQoL was impaired in all domains in patients with AP-4-HSP (mean score: 59.6 ± 12.6 [SD]), with no significant difference between the 4 subtypes. Age, as a surrogate for disease duration, and Spastic Paraplegia Rating Scale scores, as an indicator for corticospinal tract dysfunction and motor impairment, correlated with lower CPCHILD scores (Pearson r = −0.31, p = 0.01 and r = −0.52, p < 0.0001, respectively). Patients with tetraplegia showed lower CPCHILD scores compared with individuals with diplegia or no spasticity. Wheelchair dependence reduced HRQoL in all domains. The presence of seizures, including medically refractory epilepsy, was not associated with lower CPCHILD scores. Standardized assessment of caregiver priorities identified several areas of high importance to HRQoL. Conclusions: We show that the CPCHILD questionnaire, developed for use in children with cerebral palsy, can be used to assess HRQoL in patients with childhood-onset complex hereditary spastic paraplegia. HRQoL is reduced in patients with AP-4-HSP and correlates with the degree of motor impairment. These results provide a framework for medical decision making and a baseline for the future development of treatment guidelines and interventional trials.